Prevalence and determinants of overweight/obesity among school-aged adolescents in the United Arab Emirates: a cross-sectional study of private and public schools - Baniissa, Wegdan (BMJ Open, 2020)
OBJECTIVES: To estimate the prevalence and predictors of obesity among adolescents in the United Arab Emirates. DESIGN: Cross-sectional study. SETTING: Private and public secondary schools. PARTICIPANTS: Adolescents aged 13–19 years; 434 (46.6%) from private schools and 498 (53.4%) from public schools. MEASURES: Self-report questionnaires were used to assess adolescents’ sociodemographic factors, fruit/vegetable (F/V) intake and physical activity. Participants’ weight, height, waist circumference (WC), hip circumference and body fat percentage (%BF) were measured, and waist-to-height ratio (WHtR), waist-to-hip ratio (WHR) and body mass index (BMI) were calculated. Overweight/obesity was determined by BMI ≥85th percentile for age, abdominal obesity (AO) (WC, WHtR and WHR) and %BF. RESULTS: A total of 34.7% of participants were overweight/obese (BMI ≥85th percentile) and 378 (40.6%) had high %BF. AO was noted in 47.3%, 22.7% and 27.1% of participants, based on WC, WHR and WHtR, respectively. Significantly more participants from public schools were overweight/obese (37.8% vs 31.1%) and had greater AO (based on WC, WHR, WHtR) compared with those from private schools. Predictors of obesity based on BMI were: consuming less than five servings of F/V (adjusted OR (AOR) 2.41, 95% CI: 1.73 to 3.36), being physically inactive (AOR 2.09, CI: 1.36 to 3.22) and being men (AOR 3.35, 95% CI: 2.20 to 5.10). Predictors of AO were being men (WC: AOR 1.42, 95% CI: 1.01 to 2.00; WHtR: AOR 2.72, 95% CI: 1.81 to 4.08); studying at public school (WHR: AOR 1.67, 95% CI: 1.06 to 2.66); being Emirati (WHR: AOR 0.62, 95% CI: 0.43 to 0.90); consuming less than five servings of F/V (WC: AOR 1.71, 95% CI: 1.27 to 2.30; WHtR: AOR 1.46, 95% CI: 1.05 to 2.03), and being physically inactive (WC: AOR 1.63; 95% CI: 1.13 to 2.35). CONCLUSIONS: Focused interventions are needed to combat obesity while considering AO indicators and BMI to diagnose obesity in adolescents.